RANCANGAN PEMBUATAN ALAT PRES BERBASIS ULIR PADA MESIN PEMARUT DAN PEMERAS SANTAN KELAPA - Hajis, Abdul; Arifin, Zaenal (University of Riau Kepulauan, 2023)
The process of grating coconut into grated coconut, and then the process of making grated coconut into pure coconut milk, which is carried out by people living in rural areas to this day is still very traditional. The work is done manually (using hands) to produce 7.2 kg/hour of grated coconut or 3.6 liters/hour of thick coconut milk. To make the process smoother, the squeezing needs to be done mechanically, namely using a grated coconut press machine. The machine is designed based on a Screw Press system with 1⁄4 HP 1450 rpm electric motor power using a pulley belt transmission. Squeezing power refers to the capacity of the grated coconut that can be accommodated in the pressing tube (squeezing power by hand is usually done by coconut oil producers and some traditional food stall entrepreneurs in rural areas). The prototype of this machine is capable of producing .6 liters/hour of thick coconut milk, which has the same quality (color, smell and texture) as that squeezed manually.